2004
DOI: 10.1902/jop.2004.75.3.470
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic and Dimensional Evaluation of Free Connective Tissue Grafts in Prosthetically Treated Patients: A 1‐Year Clinical Study

Abstract: Although these results are not conclusive, mostly due to a lack of a large enough sample population, the statistically significant results shown in this investigation tend to support the use of gingival augmentation procedures in prosthetic patients with insufficient keratinized gingiva and/or shallow or absent vestibules, when they cannot demonstrate adequate plaque control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 28 publications
6
53
1
4
Order By: Relevance
“…At 1 month, FGG dimensions (width, length, and area) were reduced by 35%, 18%, and 46% and 25%, 17%, and 37% in smokers and non‐smokers, respectively. The 1‐month FGG width shrinkage results are consistent with the handful of studies that have previously documented width shrinkage at 1 month, 14,17,38‐40 where the reported shrinkage was 25%, 14,17 28%, 40 32%, 38 and 38% 39 . Only one other study 39 provides 1‐month results on FGG length or area changes for sutured grafts, and the respective values were 4% and 41% 39 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…At 1 month, FGG dimensions (width, length, and area) were reduced by 35%, 18%, and 46% and 25%, 17%, and 37% in smokers and non‐smokers, respectively. The 1‐month FGG width shrinkage results are consistent with the handful of studies that have previously documented width shrinkage at 1 month, 14,17,38‐40 where the reported shrinkage was 25%, 14,17 28%, 40 32%, 38 and 38% 39 . Only one other study 39 provides 1‐month results on FGG length or area changes for sutured grafts, and the respective values were 4% and 41% 39 .…”
Section: Discussionsupporting
confidence: 87%
“…Soehren et al 12 treated 10 smokers and 10 non‐smokers; their reported data allow calculation of 3‐month width shrinkage in seven smokers (≥0.5 pack/day) and six non‐smokers as 29% and 36%, respectively. Orsini et al 40 used free connective tissue grafts, instead of FGG, to evaluate outcomes dimensionally in 16 treated patients, 3 of whom were smokers. The authors stated that smokers seemed to have higher shrinkage, but the small number of smokers did not allow statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Orsini et al 6 compared the results of CTG and no gingival augmentation in similar clinical scenarios by using the following parameters: dimensional changes of CTG (mm), color blending with the adjacent tissues (F = fair or E = excellent), and health status in the adjacent gingival margin and periodontal tissues (gingival index, plaque index, probing depths, and clinical attachment levels). Orsini et al 6 compared the results of CTG and no gingival augmentation in similar clinical scenarios by using the following parameters: dimensional changes of CTG (mm), color blending with the adjacent tissues (F = fair or E = excellent), and health status in the adjacent gingival margin and periodontal tissues (gingival index, plaque index, probing depths, and clinical attachment levels).…”
Section: Introductionmentioning
confidence: 99%
“…Various amounts of graft shrinkage during the healing period have been reported which ranges between 12% and 48% [15][16][17]. Studies show that shrinkage occurs during the first year after surgery and the width of keratinized tissue remains stable after that [18,19]. The results of the case series have demonstrated changes at an individual level.…”
Section: Discussionmentioning
confidence: 88%